A Comprehensive Study of The Criminalization of Parental Violence Against Children (Legal, Human Rights, and Sharia Perspectives) - Herni Ramayanti; Rabith Madah Khulaili Harsya; Asyri Febriana; Nabain Idrus; Syamsul Efendi (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study is a qualitative study with a descriptive approach, namely an approach that aims to describe each main topic in this study, including the criminalization of children by parents from the perspective of Indonesian law, the criminalization of children by parents from the perspective of human rights, and the criminalization of children by parents from the perspective of sharia law. The data used in this study are secondary data that researchers obtained from books, scientific articles, laws and regulations, websites, and so on. The data obtained was analyzed using the stages of data collection, data selection, data reduction, and drawing conclusions. The conclusion in this article show that from an Indonesian legal perspective, criminalization or violence against children is subject to varying penalties depending on the type of criminalization or violence committed. In physical violence in the form of abuse, the maximum penalty is three years and six months and/or a fine of Rp. 72,000,000.00 for minor abuse. The maximum penalty is five years if the child experiences serious injuries with a fine and/or Rp. 100,000,000.00 for abuse that causes serious injuries. And is subject to a maximum of fifteen years imprisonment and/or a fine of Rp. 300,000.00 if the child dies. If the violence is committed by a parent, a third of the sentence is added. In contrast to physical criminalization, parents can be sentenced to a minimum of five years imprisonment and a maximum of fifteen years if they commit sexual violence against their child, an additional one-third. From a human rights and Islamic law perspective, this is a heinous and prohibited act and the perpetrator must be punished according to the level of criminalization and violence.